Selection efficiency for increasing physic nut oil content - Rocha, Rodrigo Barros; Ramalho, André Rostand; Teixeira, Alexsandro Lara; Laviola, Bruno Galvêas; Silva, Francisco Célio Gomes da; Militão, Júlio Sancho Linhares Teixeira (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to estimate the genetic parameters of physic nut (Jatropha curcas) grain quality traits and to quantify the genetic progress with selection. Seed oil content, and seed, kernel, and shell weights of 120 plants, randomly selected in a commercial planting, were evaluated at 36 and 48 months. Genetic progress was quantified by the evaluation of direct gains and by the use of selection indexes. The genotype x measurement interaction was significant for all evaluated traits; therefore, there are genotypes with different behavior in the two cropping seasons. The genetic parameters indicated a higher proportion of genotypic variation in the expression of the evaluated traits, and a trend of the genotypes to maintain their genetic superiority over time was observed. The genotype‑ideotype selection index resulted in higher genetic gains and promoted a more balanced alteration in the trait means. The direct selection for kernel weight results in genetic gains similar to those obtained with the use of the selection indexes.